RICKETS IN CHILDREN - A CONTINUOUS CHALLENGE - Dan Moraru; Evelina Moraru; Laura Bozomitu; Bogdan A. Stana (Amaltea Medical Publishing House, 2008)
Rickets in children is a frequent nutritional disorder met even nowadays in clinical practice, with predominence of light and medium forms. Authors discuss the epidemiological and disease mechanisms' aspects, revealing specific risk factors for age groups along with hystological and pathogenical aspects. There are detailed descriptions of clinical and radiological aspects of disease and elements of positive and differential diagnosis. Prophylactic and curative treatment are issued after Bucharest ICMC, whose recommendations are an excellent guide. Finally, authors elaborate evolutive considerations in the absence of treatment and under specific therapy with vitamin D